2022
DOI: 10.1002/vms3.923
|View full text |Cite
|
Sign up to set email alerts
|

The effects of green tea in the diet of broilers challenged with coccidiosis on their performance, carcass characteristics, intestinal mucosal morphology, blood constituents and ceca microflora

Abstract: Background Coccidiosis is an endemic protozoal disease of chickens normally controlled by ionophores. However, coccidiostats are also antibiotics, and evidence of resistance in both coccidia and bacteria may develop and reduce antibacterial activity in humans. This has led to a search for natural coccidiostats, such as green tea. Objectives To study the effects of supplementing broilers with various levels and types of green tea, in comparison to use of a conventional coccidiostat or a control, unsupplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Morphological properties of the small intestine mucosal surface provide insight into the absorptive process and developmental progression of the small intestine (Yang et al., 2007 ). An increase in the VH/CD ratio is associated with increased digestion and absorption in the gut because longer villi and shorter crypts give greater surface area (Jelveh et al., 2022 ). Our findings revealed that while the reduction of ME and CP–LAA levels did not have a detrimental effect on the duodenal morphology, it did lead to a decrease in the VH and VSA in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological properties of the small intestine mucosal surface provide insight into the absorptive process and developmental progression of the small intestine (Yang et al., 2007 ). An increase in the VH/CD ratio is associated with increased digestion and absorption in the gut because longer villi and shorter crypts give greater surface area (Jelveh et al., 2022 ). Our findings revealed that while the reduction of ME and CP–LAA levels did not have a detrimental effect on the duodenal morphology, it did lead to a decrease in the VH and VSA in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…Jelveh et al. ( 2022 ) used three levels of green tea extract (0.2, 0.3 and 0.4 g/kg) and powder (1, 2 and 3 g/kg) in the broilers’ diet and reported that green tea increased VH and VW in the different intestinal parts, compared with control. When studying the effect of orange essential oil on the histology of the intestine of broiler chickens, Erhan and Bolukbasi ( 2017 ) found that using 3 mL/kg of oil in the diets increased the VH.…”
Section: Discussionmentioning
confidence: 99%
“…Hasanpour et al (2010 reported that the VH in the duodenum and jejunum compared to the control group significantly developed in the treatment containing green tea. Jelveh et al (2022) used three levels of green tea extract (0.2, 0.3 and 0.4 g/kg)…”
Section: Treatmentsmentioning
confidence: 99%
“…There are other feed additives that can have beneficial effects in controlling disease, such as sumac berries and thyme, but they are not available in sufficiently large quantities and, to make a major contribution, many farmers would have to transition to growing them [ 61 ]. Green tea is potentially available in large quantities and has beneficial antibacterial properties to potentially control coccidiosis without using coccidiostat antibiotics [ 62 ].…”
Section: Options For Farmers To Address Animal Welfare Challengesmentioning
confidence: 99%